Relationship of Early Childhood Neglect and Abuse with Emotion Regulation and Emotion Recognition in Adolescents (Global Journal of Human-Social Science, 2018)
Background Different patterns of childhood neglect and abuse are related with the level of seriousness of mental issue in adulthood An investigation of this nature is essential to understand developmental trajectory of neglect and abuse and to base any intervention plan for affected individuals and to build up a risk alleviating techniques as primary prevention Aim To examine relationship of Childhood Neglect and Abuse with Emotion Regulation and Emotional Recognition in adolescents Method A purposive sample of 140 children studying in English and Hindi medium schools located in Delhi and NCR region India was taken to test the hypotheses Willing individuals of age range from 16 to 18 years of either sex were administered a set of self-administered questionnaires viz General Health Questionnaire GHQ Toronto Alexithymia Scale TAS Difficulties in Emotion Regulation Scale DERS and The Childhood Experience of Care and Abuse Questionnaire CECA for collecting the data Results The analysis indicated that GHQ cut-off score did not differ significantly on any of the study variables and the examined constructs sexual abuse physical abuse parental loss with difficult in emotion regulation and neglect physical abuse with alexithymia were positively correlated with Difficulty as measured on Emotion Regulation Scale and Toronto Alexithymia Scale Results also indicated that sexual abuse and physical abuse were significantly predicting difficulty in emotion regulation R 2 0 38 p 0 01 and alexithymia R 2 0 35 p 0 01 Conclusions Deficits in emotion regulation and emotion recognition were ubiquitous in children reporting of adverse childhood experience such as neglect and abuse Sexual and physical abuse emerged as significant variables accounting for maximum variance in criterion variables viz emotion regulation and recognition
Keywords: childhood neglect and abuse; emotion regulation; emotion recognition